Field parasitism of Opisina arenosella pupae and laboratory development of Trichospilus pupivorus on Galleria mellonella - HONG-UNG NGUYEN; THI-THANH-NGA SON; CHI-HIEU PHAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nguyen H-U, Son T-T-N, Phan C-H. 2026. Field parasitism of Opisina arenosella pupae and laboratory development of Trichospilus pupivorus on Galleria mellonella. Biodiversitas 27 (3): d270316. https://doi.org/10.13057/biodiv/d270316. The black-headed caterpillar, Opisina arenosella is a major coconut pest in Asia and has caused serious damage in Vietnam’s Mekong Delta since its first detection in 2020. Parasitoid wasps play an important role in pest control, among which Trichospilus pupivorus is an effective pupal parasitoid of O. arenosella. In addition, larvae and pupae of Galleria mellonella are widely used as alternative hosts for laboratory rearing of beneficial insects. This study investigated the field occurrence of T. pupivorus in coconut orchards of Tra Vinh province and evaluated its development on G. mellonella to support laboratory mass rearing. Field surveys were conducted in 15 infested orchards, where a total of 1,500 O. arenosella pupae were collected from 150 coconut trees to estimate parasitism rates. Five parasitized pupae from each orchard were reared individually to quantify progeny production per parasitized O. arenosella pupa. The results showed that T. pupivorus was detected in 86.7% of orchards and 72.7% of sampled trees, while the mean orchard-level parasitism rate was 17.1±7.75%. Mean progeny production was 462.5±91.4 individuals per parasitized O. arenosella pupa. Under controlled insectary conditions (27±1°C, 75±1.5% RH, 12L:12D photoperiod), the parasitoid completed development on G. mellonella pupae in approximately 16 days, producing 118.3±46.7 individuals per G. mellonella pupa with a strongly female-biased sex ratio (>97%). These findings provide baseline quantitative information on the field occurrence and laboratory performance of T. pupivorus associated with O. arenosella in coconut agroecosystems.